Assessing the potential to use serious gaming in planning processes for sanitation designed for resource recovery. Issue 145 (July 2023) - McConville, Jennifer R.; Billger, Monica; Niwagaba, Charles B.; Kain, Jaan-Henrik
Abstract: There is an urgent need for innovations in the sanitation sector to minimize environmental impacts and maximize resource recovery. Uptake of innovations may require changes in established technical practices, organisational norms and/or individual behaviours. Achieving change in any of these areas requires influencing cognitive, normative and relational learning processes. Serious games have been identified a potential tool for planners and environmental managers to influence such learning processes. This study designed the serious game RECLAIM to share knowledge about resource recovery from sanitation and to support attitude-change and collaboration between players. A structured framework was applied to assess if the game: 1) increased understanding of resource recovery ( cognitive learning ), 2) changed worldviews ( normative learning ), 3) led to more collaboration ( relational learning ), and 4) was a positive experience. Proof-of-concept testing of the game in Uganda found that it was positively received. The game provided cognitive learning on environmental and health impacts, resource recovery, and sanitation in general. Players gained an appreciation of the need for collaboration and it was deemed to have the potential to influence worldviews of a larger stakeholder group. Future recommendations include embedding the game in planning processes, including several gaming sessions that would strengthen cognition learning and the potential for changing practices. Highlights: A game designed to influence cognitive, normative & relational sanitation learning. It communicated cognitive knowledge on sanitation impacts & resource recovery. Serious gaming in planning can influence worldviews and stakeholder norms. Players gained an appreciation of the need for collaboration. Games in planning processes would strengthen potential for changing practices.